Prevalence and associated factors of repetitive strain injury of upper extremities among office workers in a government agency, Putrajaya - M. K., Wan; Hamedon, Titi Rahmawati; Zainuddin, Huda (Community Health Society Malaysia, 2016)
Background: Office workers are at risk for of developing repetitive strain injury (RSI) of upper extremities due to various factors at workplace. RSI is a work related disorder manifested with regular symptoms of musculoskeletal and nervous system, which could affect work productivity. In Malaysia, more than 50% of the workforce is comprised of office workers. However national data on RSI prevalence is limited. A local study conducted in 2014 has shown that the prevalence of RSI can be as high as 67.2% among university workers which included office workers. Materials and Methods: A cross sectional study was conducted in the headquarters of Department of Statistics, Malaysia (DOSM) using pre-tested self-administered questionnaire. Office workers were randomly selected via stratified sampling. Ethical approval had been obtained from the Ethics Committee for Research Involving Human Subjects, Universiti Putra Malaysia (UPM). Data obtained was analyzed using Statistical Package for the Social Sciences (SPSS), version 22.0. Result: The response rate was 85.7%. The results showed that the prevalence of RSI of upper extremities among the respondents was 20.8%, which was quite low compared to those in other studies. The findings revealed that RSI of upper extremities was significantly associated with job group, frequency and duration of doing overtime work, work demand, break time quality and feeling sleepy at work. Conclusion: The prevalence of RSI of upper extremities among DOSM office workers is low. It is recommended to conduct further study to explore the reason associating break time quality and feeling sleepy among office workers with the development of RSI.